GOOD CORPORATE GOVERNANCE PRINCIPLES ON INTERNET INTERMEDIARY COMPANIES IN PROTECTING THE PRIVACY OF PERSONAL DATA IN INDONESIA - Saskia Kusumawardani; Sinta Dewi Rosadi; Elisatris Gultom (Yustisia Jurnal Hukum, 2020)
The implementation of good corporate governance (GCG) is the main foundation of companies that needs to run their business activities for a long period. Along with the development of technology and information, the implementation of GCG is increasingly needed for internet intermediary platform providers in carrying out their business activities. The implementation of GCG principles can also reduce the risk of failure in protecting privacy of personal data on the platform. The related principles are transparency, accountability, and responsibility principle by taking into account a number of laws and regulations such as Law No. 11 of 2008 as amended by Law No. of 2016 concerning Amendments to Law No. 11 of 2008 concerning Information and Electronic Transactions (ITE Law), Government Regulation No. 71 of 2019 (GR 71/2019), and Ministry of Communication and Information Regulation No. 20 of 2016. This research will use a normative juridical research method that takes into account the provisions of the legislation and other relevant documents. As a result, the implementation of  GCG is not fully implemented in the case of failure in protecting privacy of personal data in internet intermediary company (PT Bukalapak), thus the legal attempt that can be applied to manifest the company’s liability refers back to ITE Law, GR 71/2019, and Ministry of Communication and Information Regulation 20/2016 which are compensation and administrative sanctions.